O trabalho e os desafios do professor coordenador na rede municipal de Rio Claro - Ferri, Thais Helena Jordão Bartiromo [UNESP] (2013)
The present study focuses on research Coordinator Teacher in the municipal Rio Claro-SP. The teacher coordinator has been one of the actors discussed within the school, since their work is constantly (re) construction from guidelines and educational politics that fall. The research focuses on the role that emerging Teacher Coordinator of the school setting as a key element in the articulation and mediation of relations and especially the process of continuing education (in-service) teacher in the school context. We understand that he has an important function for the school institution and its work in the continuing education of teachers may result in a positive impact on student learning and the best professional development of teachers. In this sense the setting of the research study is the school as a place of teacher education (continuing education), and that takes time Pedagogic Work Collective (HTPC) as a privileged space and time for such training. The main question of this research probes the challenges of coordinating teacher in their relations with the teachers in the school routine. From that point, we had the following objectives: (a) identify the conceptions of Professor Coordinator about your role with teachers; (b) analyze the challenges of Professor Coordinator in your routine and referrals in HTPCs. As a means to find the answers sought in this study chose to qualitative research, with interpretive approach, with the social constructivism paradigm. The survey covered four schools of the municipal school of Rio Claro-SP attending the school. In each of these schools was considered as a participant teacher coordinator and a total of four participants. Among the instruments of data collection, were selected source documents, observation, semi-structured interviews and content analysis. The concluding remarks of this study are presented as possible reflections on the work and the challenges faced by Professor Coordinator in...